2021
DOI: 10.3390/ijms22136802
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into Red Blood Cell Microcytosis upon mTOR Inhibitor Administration

Abstract: The aim of this study was to evaluate the effect of everolimus, a mammalian target of rapamycin (mTOR) inhibitor, on red blood cell parameters in the context of iron homeostasis in patients with tuberous sclerosis complex (TSC) and evaluate its effect on cell size in vitro. Everolimus has a significant impact on red blood cell parameters in patients with TSC. The most common alteration was microcytosis. The mean MCV value decreased by 9.2%, 12%, and 11.8% after 3, 6, and 12 months of everolimus treatment. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…In our study, the elevated EPO production was able to compensate and preserve hemopoiesis. Previous studies have demonstrated that microcytosis or anemia are induced in mTOR inhibitor-treated subjects (7,(13)(14)(15)(22)(23)(24). EPO is also known to inhibit hepcidin production (25)(26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In our study, the elevated EPO production was able to compensate and preserve hemopoiesis. Previous studies have demonstrated that microcytosis or anemia are induced in mTOR inhibitor-treated subjects (7,(13)(14)(15)(22)(23)(24). EPO is also known to inhibit hepcidin production (25)(26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have demonstrated that mTOR inhibitors induce microcytosis, possibly due to inhibition of erythroid precursors (22,23) and that these effects are not overcome by increasing available iron in the culture environment (23). This microcytosis is reversed by withdrawal of mTOR inhibitors (7,13,15).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations